Pengembangan Alat Peraga Taktual Model Atom untuk Siswa Tunanetra Kelas VIII - Wahyu Triningsih; Winarti Winarti (INKLUSI, 2014)
The research purposes to (1) produce atomic model tactual props and material guidance of atomic model for blind student on eight grade, (2) know quality of atomic model tactual props and material guidance of atomic model for blind student on eight grade, (3) know student response toward atomic model tactual props and material guidance of atomic model for blind student on eight grade.This is a developmental research based on a procedural model. The development procedure is based on the development research procedure by Puslitjaknov Team that is adapted from Borg and Gallresearch procedure with development steps such as (1) doing product analysis that will be developed, (2) developing preliminary product, (3) experts validation and revision, (4) small scale field test and product revision, and (5) large scale field and final product. Collecting data technique by a non test research instruments are developed by such as validation sheet, appraisal sheet and student response. The analyzing data technique is done by changing the quantitative data into qualitative data.This research produced an atomic model tactual props and material guidance for blind student on eight grade. Based on the appraisal of media expert, material expert, teacher, atomic and students this prop has a very good quality.